Body work in health and social care critical themes, new agendas - Twigg, Julia (Sociology of health and illness monograph series ;, 2011)
"Body work is paid work undertaken on the bodies of others. Although it forms a central part of health and social care, its study has often been obscured or neglected. This volume is the first to directly address the concept, exploring the multiple ways in which body work features in health and social care and analyzing the meanings of this work for both those employed to do it and those on whose bodies they work. With contributions from the top international scholars in the field, the book draws on perspectives from across the medical, therapeutic, and care fields. Using a variety of methodological approaches, from life history analysis to ethnographic studies and first person accounts, this book highlights the embodiment of health and social care and the contribution of this emphasis to new directions in sociology. "--